Sex-specific socioeconomic risk factors for spontaneous subarachnoid hemorrhage-a case-control study during the 5 years before ictus - Elisabeth Ronne-Engström; Emilie Friberg (Frontiers Media S.A., 2024)
BackgroundThere is a difference in the incidence of spontaneous subarachnoid hemorrhage (SAH) between sexes, with the majority of cases occurring in female patients. Although this phenomenon has been studied from a medical perspective, the reasons for the predominance of female cases are still unclear. Non-medical factors, such as a patient's socioeconomic situation, can differ between female and male patients, with health implications. The aim of the study was to identify socioeconomic profiles for both sexes that may be vulnerable to developing SAH. This information could potentially be used for active preventive health efforts.MethodsThis study was based on a 7-year consecutive cohort of 890 patients with SAH treated at Uppsala University Hospital, along with a sex- and age-matched 5:1 control group from Statistics Sweden. The collected information included demographic data, income that was analyzed through "earnings" (EAs), which is defined as the sum of income and other economic compensations related to work, and "disposable income" (DI), which is the net amount that an individual can use. Pension and sickness-related absence from work were measured using early pension (EP), old age pension (OAP), sickness absence (SA), and disability pension (DP). Univariate and multivariate analyses were used.ResultsAmong the women, the socioeconomic risk profile for SAH included lower education, unemployment, being registered as living single, residing in a sparsely populated municipality, and increased age. For the men, the risk profile included residing in a sparsely populated municipality and changes in civil status. Both women and men with SAH had lower EAs and DI compared to the controls. Notably, a significantly higher proportion of the women with SAH received DP compared to the controls.ConclusionResiding in a sparsely populated area was associated with an increased risk for SAH for both women and men. The women with SAH were more economically vulnerable, whereas the men faced a different type of vulnerability related to changes in civil status. We suggest that healthcare organizations use this information to identify individuals at risk and actively implement preventive measures according to stroke guidelines for both groups.